Interdisciplinary approaches in modern zoology (Zoological Records and Reviews, 2025)
Modern zoology has undergone a profound disciplinary transformation: questions that were once the exclusive domain ofnatural history and field biology now draw equally on molecular genetics, computational data science, physics-inspiredmodelling, social science, economics, and engineering. This interdisciplinary convergence is not merely methodological-- it reflects a conceptual reorientation in which the boundaries between zoology and neighbouring disciplines havebecome permeable, generating hybrid research fields (landscape genomics, conservation social science, movementbiophysics, zoonotic epidemiology, animal-inspired robotics) whose most impactful outputs emerge precisely from thedisciplinary interfaces. This review synthesises evidence from 182 primary studies (2010-2025) examining the structure,productivity, and conservation impact of interdisciplinary zoological research, evaluating seven major disciplinaryintegration domains: zoology-genomics, zoology-data science and AI, zoology-physics and engineering, zoology-socialscience, zoology-medicine (One Health), zoology-economics (natural capital), and zoology-earth observation.Bibliometric analysis of 14,240 interdisciplinary zoological publications (2015-2024) finds that papers crossing two ormore disciplinary boundaries receive mean 2.4-fold higher citations than single-discipline zoological studies, produce3.2-fold more policy documents, and attract 1.8-fold more media coverage. However, interdisciplinary research facesstructural barriers -- incompatible publication cultures, disciplinary funding silos, career incentive misalignments, andmethodological translation challenges -- that systematically undermine its production relative to its impact. A frameworkfor designing, funding, and evaluating interdisciplinary zoological research programmes aligned with EU Horizon Europepartnership requirements is presented.
Keywords: Horizon Europe; disciplinary integration; research collaboration; bibliometrics; natural capital; One Health; landscape genomics; conservation social science; modern zoology; interdisciplinary research